Reducing Railway Noise with Porous Sound-Absorbing Concrete Slabs - Caiyou Zhao; Ping Wang; Li Wang; Dan Liu (Advances in Materials Science and Engineering)
The effect of porous sound-absorbing concrete slabs on railway noise reduction is examined in this paper. First, the acoustical absorption coefficients of porous concrete materials with various aggregate types, gradations, fibre contents, and compaction indexes are measured in the laboratory. The laboratory results show that porous concrete that uses a composite of expanded perlite and slag as aggregate can not only obtain good acoustical absorption properties but also satisfy mechanical requirements. Also, the gradation of the combined aggregate has a significant effect on the acoustic absorption performance of the porous concrete, with an optimal aggregate gradation of 1~3 mm. Furthermore, the fibre content and compaction index affect both the strength and the acoustic absorption property of the porous concrete, with the optimum value of 0.3% and 1.6, respectively. Then, the findings from the laboratory studies are used to make porous sound-absorbing concrete slabs, which are applied in a test section. The measurements indicate that porous sound-absorbing concrete slabs can significantly reduce railway noise at different train speeds and that the amount of the noise reduction changes roughly linearly with speed when the train is traveling at less than 200 km/h. The maximum noise reduction is 4.05 dB at a speed of 200 km/h.